Reconfiguration Testing for Cooperative Autonomous Agents - Saglietti, Francesca; Winzinger, Stefan; Lill, Raimar (Computer Safety, Reliability, and Security, SAFECOMP 2015 Workshops, 2015)
In order to verify reconfiguration of interacting autonomous agents to be exclusively beneficial and never hazardous to cyber-physical systems, this article suggests a systematic approach based on incremental model-based testing and illustrates its application to cooperating mobile robot
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.lsinfs_1.reconf_7
Keywords: Cyber-physical systems; robots; autonomous agents; cooperation; reconfiguration; CPN modelling; incremental testing